CUCI NEGERI DAN TINDAKAN BERTEOLOGI: Analisis Interpenetrasi Agama Dalam Praktek Adat Di Hukurila - Agustinus O Lopuhaa; A Watloly (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2019)
The aim of this article is to explain about dynamic encaounters between Christian and cultural point of views on Cuci Negri, a Molucan local culture or adat.  An adat forms value and enriches a social identity of a local community, so do the Cuci Negri. Cuci Negri was (and still is) one tradition or ritual that shows the indigenous identity on Ambon Island, especially in some villagees of Leitimur. In Hukurila, this tradition is carried out every year on December 13th, to 16th. Since 1986, there had been interpenetration processes between the gospel and the custom, a new approach, compere to the former approach where church tend to penetrate indigenous religion or local custom. Study of the interpenetration process is expected to be a framework of contextual theology in Hukurila. The process of Cuci Negeri ritual reveals a dialectical relationship between the gospel and adat, which gives meaning to each other. This relation is not to weaken or eliminate each one, but gives a value or meaning of one another. Besides, Cuci Negeri is a way through which people of Hukurila maintain their cosmos, in order to remain sustainable for the future of their generation.